DEKOMPOSISI SAMPAH BAHAN ORGANIK RUMAH TANGGA MENGGUNAKAN CACING TANAH JENIS Eisenia fetida DAN Lumbricus rubellus - Soekmana Soma (Purifikasi, 2010)
The use of earth worms for composting organic agriculture waste, or vermiculture, has been known since early civilization. The vermiculture process for organic waste from domestic and commercial sources has been investigated only recently. The objective of vermiculture utilization is to search solution of domestic and industrial waste problems. In this study two species of worms, namely tiger worms and red worm, were used as decomposers of household wastes. These two kinds of worms converted the household wastes into vermicompost and vermicasting. The most efficient conversion was found in hardbox decomposition (70%), kitchen wastes (66%), mixed fruits and vegetables (58%), and the least was garden leaves (56%).